3D focused ion beam sectioning of zirconium oxides in Zircaloy-4 for the characterisation of cracking - Weekes, HE; Ortner, S; Qaisar, A; Lozano-Perez, S; Jurkschat, K (Elsevier, 2020)
Sequential 2D sectioning and imaging using a dual-beam focused ion beam and scanning electron microscope has been used to characterise the interconnectivity of cracks in oxide films on Zircaloy-4. Evidence of cracks perpendicular to the metal/oxide interface have been observed in multiple oxides of different thicknesses. Such vertical features are considered critical in the provision of a percolation path between the environment and innermost band of lateral cracks (closest to oxide/environment interface), in between the lateral bands of cracks and between the final band of lateral cracks and the metal/oxide interface. Given the limited occurrence of cracks perpendicular to the metal/oxide interface, localised tensile surface strains have been considered as a potential source of initiation of these cracks.